2012
DOI: 10.1124/mol.112.078865
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sphingomyelin Phosphodiesterase Acid-Like 3A Gene (SMPDL3A) by Liver X Receptors

Abstract: Liver X receptor (LXR) ␣ and LXR␤ function as physiological sensors of cholesterol metabolites (oxysterols), regulating key genes involved in cholesterol and lipid metabolism. LXRs have been extensively studied in both human and rodent cell systems, revealing their potential therapeutic value in the contexts of atherosclerosis and inflammatory diseases. The LXR genome landscape has been investigated in murine macrophages but not in human THP-1 cells, which represent one of the frequently used monocyte/macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…SMPDL3A mRNA was also up-regulated by treatment with a second LXR ligand, 22-hydroxycholesterol (data not shown). These results are consistent with other studies published while this work was underway, which demonstrated that SMPDL3A mRNA expression is increased by LXR ligands in the immortalized human leukemic THP-1 macrophage cell line and in undifferentiated human peripheral blood mononuclear cells (8,9).…”
Section: Smpdl3a Expression and Secretion Is Up-regulated By Cholestesupporting
confidence: 83%
See 1 more Smart Citation
“…SMPDL3A mRNA was also up-regulated by treatment with a second LXR ligand, 22-hydroxycholesterol (data not shown). These results are consistent with other studies published while this work was underway, which demonstrated that SMPDL3A mRNA expression is increased by LXR ligands in the immortalized human leukemic THP-1 macrophage cell line and in undifferentiated human peripheral blood mononuclear cells (8,9).…”
Section: Smpdl3a Expression and Secretion Is Up-regulated By Cholestesupporting
confidence: 83%
“…SMPDL3A was originally identified as a gene up-regulated in bladder tumor versus healthy urothelium tissue (7), and more recently it has been shown to be regulated by liver X receptor (LXR) ligands in human macrophage cell lines (8,9). Beyond these observations, little is known about the biochemistry or function of SMPDL3A.…”
Section: Increased Expression and Secretion Of Smpdl3a By Cholesterolmentioning
confidence: 99%
“…95 51,99). New targets revealed in this study include SMPDL3A, which could be another important ccRCC-specific oncogene given its role in lipid and cholesterol metabolism (61,100). Genes associated with lost superenhancers, which could only be identified with normal-tumor pairs, implicated potential tumor suppressors (EHF, MAL, GCOM1, and HOXB9) that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SMPDL3A shares 31% amino acid identity with the acid sphingomyelinase SMPD1 and is a target of a master regulator of cholesterol metabolism, liver X receptors (LXR; ref. 61).…”
Section: Researchmentioning
confidence: 99%
“…The substrate and function of SMPDL3A, however, are less clear. This enzyme is secreted by osteoclasts (8), adipocytes (9), astrocytes (10), and macrophages (11), where it is up-regulated by the activation of the liver X receptor (12,13). In the serum, SMPDL3A interacts with apolipoprotein A1 (14,15).…”
mentioning
confidence: 99%